Effect of energy input on microstructure and hardness of TIG Welded AISI 430-Ferritic stainless steel - Amuda, M.O.H.; Mridha, Shahjahan (Trans Tech Publications Ltd., Switzerland, 2011)
Studies on the weldability of ferritic stainless steel grades suggests that low heat input rate and better heat transfer dynamics are appropriate for the control of grain size and microstructural feature in thin sections. However, the optimal welding conditions to achieve combination of such characteristics have yet to be established. In the present investigation, AISI430 ferritic stainless steel is TIG welded using energy input between 0.205 and 2.05kj/mm and characterized in terms of microstructure and hardness. The microstructural characterization of the welds with varying heat input rates suggests the presence of interdendritic martensite in the fusion zone and grain boundary martensite in the HAZ in conjunction with some secondary carbide in varying proportion. The hardness values across the welds indicate that grain growth and the presence of carbides are minimized when welded with increased heat input rates that permits transformation within the dual phase regions. The study provided a new insight into the contribution of heat input rate in the production of unwanted weld microstructural features and assisted in the design of methods and techniques for tailoring weld microstructures with optimum properties.